Exploring campus architecture as a factor of expected sense of belonging - Spitzer, Amanda N., author; Graham, Dan J., advisor; Delgado, Maria, committee member; Gardner, Danielle M., committee member; Malinin, Laura, committee member (Colorado State University. Libraries, 2024)
Background: The motivation, retention, and wellbeing of the increasingly diverse college student body is related to their sense of belonging at their university. Surroundings, one of Ahn and Davis' domains of university belongingness, remains underexplored, especially its subcomponent physical buildings. Additionally, prospective students name the physical campus as a major influence on their decision regarding which college to attend, and universities utilize campus photographs strategically for recruitment. Signaling theory provides a possible mechanism by which campus physical environments may influence a university's image and sense of belonging. Still, the Greek Revival and Gothic architectural styles, common on U.S. campuses, have historic ties to discrimination and racism. Purpose: The objective of study 1 is to inspect Ahn and Davis' (2020) surroundings domain and its interaction with the personal space domain, including identity variables such as first-generation status, ethnicity and race. The objective of study 2 is to explore how three architectural styles common on U.S. campuses may affect university image and students' predicted experience, including sense of belonging. Methods: In the quantitative study 1, over 600 participants answered a belongingness survey in response to a short, standardized university description and a photograph randomized to depict a Greek Revival, Gothic, or International Style (control) university building. In the qualitative study 2, fourteen interviews were conducted with first-year college students, in which participants were directed to compare three hypothetical universities, each depicted in three photographs of campus buildings in the same architectural style (Greek Revival, Gothic, or International Style). These interviews were analyzed using thematic analysis methods. Results/Findings: Through regression analyses, study 1 indicated no effects of architectural style on belongingness (p=0.29) nor interaction effects with first generation status (p=0.48) and ethnicity (p=0.30). Preliminary descriptive analysis suggested possible moderation by race. In study 2, three themes developed. Participants' impressions of the depicted universities were rooted in the buildings' communication of higher education, meaning university image began with imageability, which in turn, influenced beliefs about students and school climate. Additionally, participants discussed their predicted experience as a function of university image. Lastly, elements of the designed environment indicated imageability and predicted experience, meaning participants used environmental factors as signals. Conclusions: Study 1 addressed a crucial, but largely unexplored, potential inequity in education and experimentally investigated Ahn and Davis' (2020) surroundings domain and its interaction with the personal space domain. Study 2 has practical applications to image-based recruitment as it suggests strategies that may boost predicted experiences and aspects of university image that are communicated through architectural style. Overall, research into the relationship between campus architecture and student outcomes can equip designers and decisionmakers to create higher education environments that empower all current students, visitors, and future students.
Keywords: higher education; signaling; university image; sense of belonging; campus environment; university architecture